Women on the Job: Transitions in a Global Economy - Sugiman, Pamela (Labour / Le Travail, 2003)
The article reviews the book, "Women on the Job: Transitions in a Global Economy," by Ann Eyerman.
Keywords: BOOKS – Reviews; EYERMAN; Ann; Nonfiction; WOMEN on the Job: Transitions in a Global Economy (Book); Women employees